Effects of drafting behind a two- or a six-beat kick swimmer in elite female triathletes - Millet, G.; Chollet, D.; Chatard, J. C.; Millet, G. P. (European Journal of Applied Physiology, 2000)
The metabolic and drag responses, together with the distance between the draftee and the leader, were studied in six female triathletes swimming behind a lead swimmer who used either a two- or a six-beat kick, at an average velocity of 1.24 m · s-1 (range 1.20-1.31). Drag was measured by passive towing. Oxygen consumption [49.1 (3.8) versus 50.4 (5.0) ml · min-1 · kg-1], blood lactate [6.7 (2.3) versus 6.8 (1.9) mM], heart rate [172 (13.6) versus 173.5 (12.5) beats · min-1), rating of perceived exertion [13.7 (1.2) versus 13.5 (1.0)], stroke rate [38.3 (1.5) versus 39.5 (1.4) cycle · min-1], stroke length [1.95 (0.09) versus 1.89 (0.15) m · cycle-1] were not statistically different between the two-beat and the six-beat kick situations. The energy cost of swimming per unit of distance [0.65 (0.06) versus 0.67 (0.08) ml O2 · m-1] and the passive drag were similar for both kicks. The distance separating the draftee from the lead swimmer was between 14 cm and 85 cm and was inversely correlated with passive drag: r=-0.82,P < 0.05, for the two-beat kick and r=-0.82, P < 0.05, for the six-beat kick. The higher the passive drag, the closer the hand of the draftee to the feet of the lead swimmer. It was of no more benefit to triathletes to draft behind a two-beat kick swimmer than behind a six-beat kick swimmer.